SURVEI SARANA PRASARANA KARETEKA DI DOJO KODIM 1004 KOTABARU - Faisal Batennie; M Imran Hasanuddin (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2022)
The aims of the research is to know about the condition infrastructure of facilities on sport of karate in Dojo kodim 1004 Kotabaru. The method of this research is used of descriptive kualitatif or survey and technique of collecting data used of the interview, observation, questionaire and documentation. Thechnique take of sampel is that purposive of sampling, and take of sample with the ceritain of purpose. This thing show with have training building with one number that located on kodim 1004 Kotabaru or 100% that include in good category, karate clothes facilities good category, hand protector in good category, shind guard in good category, chest protector in good category.The jury referee uniforms include: white shirt, gray pants, red tie, black rubber shoes without soles in good category, scoring board in good category, score board in good category, red belt and blue in good category, red and blue flags for judges in good category, whistle for referee in good category, mattress in good category, Samsak in good category. Completeness of facilities and infrastructure at the Dojo Kodim 1004 Kotabaru is quite complete. Keywords: Karate Facilities and Infrastructure, at the Dojo Kodim 1004 Kotabaru